Terapia comunitária integrativa: construção de um espaço de escuta para os trabalhadores na atenção básica da saúde - Damasceno, Regina Célia (2011)
This research, which appears in the form of a dissertation, entitled: Integrative Therapy Community: construction of a listening space to health care workers in primary care, addresses the Integrative Community Therapy (ICT) as a tool to create meeting spaces between health professionals where they can be receptive among one another. With the completion of this study aimed to analyze the ICT as a therapeutic approach and space of listening and speaking for health professionals cited here in order to identify their anxieties, doubts, worries and uncertainties arising from the context of labor relations and the impact of therapeutic experiences under the view of the participants. It was developed as an action-science research, involving several steps. The field of research was the ICT meetings of workers from the units under the Family Health Strategy of Northern Health Districts I and II of the city of Natal, using a qualitative approach. The interpretation of data collected was based on content analysis proposed by Bardin. Finally, this study showed the ICT as a space for dialogue and sharing, with repercussions on labor relations and expansions beyond the ICT meetings, reaching out to family and social relationships, contributing to creating bonds and solidarity networks. Under the view of the participants it was recognized as an experience that optimized the socialization, promoting the alleviation of suffering and increasing the well-being. Based on the study findings, it is inferred that ICT can be considered a viable tool for the receptiveness and humanized care of health care workers.